Linux+ Certification Bible - Kay, Trevor (Hungry Minds, 2011)
Unleash the power of CompTIA's newest certification! Linux+ is the next hot certification to come from CompTIA, the company behind A+ with a following of 250,000+ certified and growing. Linux+ Certification Bible contains everything you need to know to pass the exam as well as practical information in one comprehensive volume!